Child's Right Reflected In Henrik Ibsen's The Lady From The Sea Play (1888): Humanistic Approach - Kusumaningrum, Haslinda, Dr. Phil. Dewi Candraningrum, M. Ed (2016)
The research is proposed to analyze child's right which is respresented by the character in Henrik Ibsen's the Lady from the Sea play by Humanistic Approach. The research sets to analyze the play based on the Humanistic Approach. This study is qualitative using the play of Henrik Ibsen's the Lady from the Sea play (1888) as the object. There are two kinds of data source: primary and secondary. The primary data source is the play of Henrik Ibsen's the Lady from the Sea and the secondary data sources are some literary books and some articles related to the play. The method of collecting data in the research is library research by reading and summarising the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study is as follow: first, children could express their artistic skill. Secondly, child right's access to appropriate information, information is a kind of the important means to know everything. Thirdly, children right to freedom of thought. Based on the analysis above, it is clear to the researcher to state that the hierarchical needs and child rights which are suitable with the main idea of Henrik Ibsen viewed by humanistic approach